Determination of the Prevalence of Postpartum Depression and Its Affecting Factors in Turkish Mothers and Syrian Refugee/Asylum Seeker Mothers - Canan Uçakcı Asalıoğlu; Büşra Karagöl; Şengül Yaman Sözbir; Mine Türkmen (AVES, 2024)
Aim: This study aimed to determine the prevalence of postpartum depression and the factors that influence postpartum depression in Turkish and Syrian refugee mothers. Methods: The participants were administered the Personal Information Form and the Edinburgh Postnatal Depression Scale in the 6th week of the postpartum period. While the number of Turkish mothers participating in the study was 66, the number of Syrian mothers was 71. The study was conducted in Çubuk Halil Şıvgın State Hospital in 2022. Results: The postpartum depression prevalence was found to be 16.7% in Turkish mothers and 0% in Syrian mothers. Turkish mothers' postpartum depression mean score was found to increase due to factors such as being exposed to social violence by the spouse, having had an abortion before, having had a stillbirth before, living in a nuclear family, losing a child before, having an acute social problem in the postpartum period, having full-term delivery, and being primipara. Syrian mothers' postpartum depression mean score (p < .05) was found to increase due to factors such as having had an abortion before, experiencing problems during pregnancy, experiencing an acute social problem in the postpartum period, being primigravida, and losing a child before. Conclusion: The postpartum depression rate was found to be 2.29 times higher in Turkish mothers compared to Syrian mothers.